Analisis Pengendalian Internal Kas Pada Klinik Mata XYZ Sidoarjo - Ika Risky Nurfadilah; Moh. Agung Surianto (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
Internal control is very important for companies, especially in managing cash. The method used in this research is descriptive qualitative method. The results of the study show that the internal control of cash at the XYZ Sidoarjo Eye Clinic is like what. The results showed that the implementation of the internal control system, especially cash receipts and disbursements carried out by the XYZ Sidoarjo Eye Clinic, was sufficient, according to theory. It's just that at the point of division of tasks and responsibilities there are still multiple functions due to limited human resources so that internal checking is ineffective and also the cash disbursement document has not been numbered sequentially to facilitate evaluation. Companies should carry out control of cash receipts and disbursements in accordance with the principles of internal control of the company